CATEGORY SHIFTS IN TRANSLATING TEXT FROM ENGLISH INTO INDONESIAN (AN APPLIED LINGUISTICS STUDY) - Arif Topan, Tegar (Universitas Sebelas Maret, 2019)
ABSTRACTThis paper is conducted in order to find out the shifts in novel of Magnus Chase and the Gods of Asgard into Indonesian. Shifts are inevitable in rendering text. According to Catford (1965:80) in Hatim (2001:15) classified the translation shifts into two major types of shifts are identified: Level Shift and Category Shift. Category shift could be as structure, unit, class, and intra-system shift. Problems discussed in this research: 1) what kinds of category shifts found in the novel of Magnus Chase and the Gods of Asgard? 2) what is the dominant category shift found in the novel of Magnus Chase and the Gods of Asgard? The data of this research were taken from the novel of Magnus Chase and the Gods of Asgard and its translation by Reni Indardini. The findings would show: 1) all kinds of category shifts found in the novel of Magnus Chase and the Gods of Asgard, 2) the dominant category shift found is unit shift.Keywords: literature, linguistics, translation, shifts, category shift AbstrakMakalah ini dibuat untuk mengetahui perubahan dalam penerjemahan pada novel Magnus Chase and the Gods of Asgard ke dalam bahasa Indonesia. Pergeseran tidak bisa dihindari dalam menerjemahkan teks. Menurut Catford (1965: 80) dalam Hatim (2001: 15) mengklasifikasikan pergeseran terjemahan ke dalam dua jenis pergeseran utama yang diidentifikasi: Level Shift dan Category Shift. Category Shift dapat berupa pergeseran structure, unit, class, dan intra-system. Masalah yang dibahas dalam penelitian ini: 1) jenis perubahan kategori apa yang ditemukan dalam novel Magnus Chase and the Gods Asgard? 2) apa pergeseran kategori dominan yang ditemukan dalam novel Magnus Chase and the Gods of Asgard? Data penelitian ini diambil dari novel Magnus Chase and the Gods of Asgard dan terjemahannya oleh Reni Indardini. Temuan akan menunjukkan: 1) semua jenis category shift yang ditemukan dalam novel Magnus Chase and the Gods of Asgard, 2) Category shift yang dominan ditemukan adalah unit shift.Kata Kunci: sastra, linguistik, penerjemahan, shift, category shift